PEMASARAN BAWANG DAUN DI DESA MAKAARUYEN KECAMATAN MODOINDING KABUPATEN MINAHASA SELATAN (Leek Marketing in Makaaruyen Village, Modoinding, South Minahasa Regency) - Eka M.M. Rompas; Ribka M. Kumaat; Joachim N. K. Dumais (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2020)
This study aimed to determine the marketing efficiency of leeks seen from the marketing margins and Farmer's Share in Makaaruyen Village, Modoinding District, South Minahasa Regency. This research was conducted from July to September 2018. The data used in this study were primary and secondary data. Primary data obtained through direct interviews with farmers using a list of questions that have been prepared. Whereas secondary data was obtained from related institutions and sources relevance in this study. The variables measured in this study were selling price, sales volume,Â  and marketing costs. The results showed that there were 4 forms of Marketing Channels in Makaaruyen Village. Channel I, from farmers directly to the retailers of the Pinasungkulan Modoinding Market. Channel II, from farmers to collecting traders then to retailers at Amurang Market then to the end consumers. Channel III, from farmers to collecting traders then to retailers at Karombasan Market then to end customers. Channel IV, from farmers then to collecting traders then to retailers at â€œBersehatiâ€ Market then to end consumers. The most efficient Leek Marketing was in Channel I because it had the highest share which was 87.5% and the lowest marketing margin, which was 12.5%.Keywords: Marketing, Leek